AN ANALYSIS OF SEMIOTIC RIFFATERRE IN WALT WHITMAN SELECTED POEM - Rusmitha Sipahutar; Tomi Arianto (BASIS (Bahasa dan Sastra Inggris), 2019)
The object research in the Walt whitman poem was an Semiotic analysis seen from Michael Riffaterre’s theory. This research used the descriptive qualitative method for this research. That means the method of data collection by analyzing and interpreting also described to understand the theories contained in the poem. In this qualitative research, researcher used the Semiotic theory by Michael Riffaterre in his book Semiotic of poetry as a basic concept and framework of thinking. The concept contains three point: The first was unsustainability of expression in poetry include the displacing meaning, distorting meaning, and the creating of meaning. It discussed the figurative language such as metaphor, personification and also the structure of verse. The second was Heuristic and Hermeneutic reading that has a relation with reading a verse based on language convension and overall rereading with interpretation. The last was Matrix, model, and varian is key,transformation, and description in a poem. In the Walt whitman selected poem finds some point based on the result of the analysis the data. From an analysis, the researcher concluded the dominant point in the Walt whitman poem is unsustainability of expression in poetry.